Work Life Balance and Employee Performance in City Councils: A Case of Northern City Division - Mercy Neumbe (Uganda Christian University, 2024)
This study was conducted to explore the relationship between work-life balance and employee performance in Northern Division, focusing on the effects of recognition, responsibility, and personal growth. Employing a cross-sectional research design, the study sampled 40 respondents from a population of 45 employees, selected using Slovin's formula. Both quantitative and qualitative methods were used to collect data, providing a comprehensive analysis of the variables. The findings revealed that recognition had a very weak positive correlation with employee performance, with a correlation coefficient (R) of 0.095, indicating that recognition accounted for only 0.9% of the performance variance. While some employees were motivated by formal awards like certificates, the overall impact of recognition on performance was minimal, suggesting the need for a more integrated approach to motivation. Responsibility also showed a weak positive correlation, with an R-value of 0.174, accounting for 3% of the variance. Despite employees appreciating involvement in planning and decision-making, the study underscored the necessity for more structured decision-making processes to enhance the effectiveness of responsibility as a motivator. Personal growth opportunities, including training and career advancement, exhibited a moderate positive correlation with performance, with a Pearson R-value of 0.292 and a significance level of 0.023, indicating a statistically significant, though moderate, impact. However, inconsistencies in the encouragement and availability of these opportunities were noted, suggesting that enhanced support for personal development could improve outcomes. The study concluded that while recognition, responsibility, and personal growth influenced performance, their individual impacts were limited, with personal growth having the most significant effect. The study recommended that Northern Division strengthen its recognition programs, ensure consistent and inclusive decision-making processes, and enhance support for training and development to improve overall employee performance.